Acidemia in Neonates With a 5-Minute Apgar Score of 7 or Greater: What are the Outcomes?. Issue 3 (September 2017) - Sabol, B.A.; Caughey, A.B.
Abstract : ( Am J Obstet Gynecol . 2016;215(4):486.e1–e6) The collection of fetal cord blood gasses at the time of delivery can be useful in the prediction of adverse outcomes associated with acidemia, such as cerebral palsy, long-term neurological deficits, neonatal death, multiorgan dysfunction, hypoxic ischemic encephalopathy, and seizures. However, universal umbilical cord blood gas analysis at the time of delivery is not a standardized practice, and the collection of fetal cord blood gases varies among institutions and providers.